2009
DOI: 10.1007/s11270-009-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbial Community Activity, Abundance and Structure in a Semiarid Soil Under Cadmium Pollution at Laboratory Level

Abstract: Cadmium (Cd) pollution can alter soil flora and fauna, as well as the microbial community associated with the main biogeochemical cycles of a soil. The present study was conducted to investigate the effect of two different concentrations of Cd pollutant, 6.5 mg kg −1 (low level) and 12.5 mg kg −1 (high level) on microbial community activity, abundance, and structure in a semiarid soil after a 60-day incubation period at laboratory level. Available Cd, water soluble carbon (WSC), microbial biomass carbon (C mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…No Nuclearia sequences were detected in the clones, conversely to what was expected from the in silico analysis. This is in agreement with other studies involving this primer set in which only fungal sequences were detected [30] , [33] , [35] , [42] and may be related to a relatively low abundance of Nuclearia (only 9 taxa recorded in the Genbank database).…”
Section: Resultssupporting
confidence: 92%
“…No Nuclearia sequences were detected in the clones, conversely to what was expected from the in silico analysis. This is in agreement with other studies involving this primer set in which only fungal sequences were detected [30] , [33] , [35] , [42] and may be related to a relatively low abundance of Nuclearia (only 9 taxa recorded in the Genbank database).…”
Section: Resultssupporting
confidence: 92%
“…Molecular techniques such as high-throughput sequencing techniques have been used to evaluate the changes in microbial community due to HMs pollution (Ros et al, 2009;Gołębiewski et al, 2014). Changes in soil microbial community structure and diversity could serve as biomarkers to study the effect of HMs on soil health (Vinhal-Freitas et al, 2017;Li et al, 2020b;Di Cesare et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Berg observed that the relative abundance of bacterial groups changed within a Cu gradient (20 to 3537 mg/kg), which originated from CuSO 4 contamination over 85 years ago (Berg et al 2012). Margarita discussed the diversity of taxonomic groups after a 60-day incubation period with Cd concentrations reaching 12.5 mg/kg (Ros et al 2009). However, these previous studies ignored the ubiquitous mild heavy metal pollution effect on soil microbes, which was apparent in the iron mine in our studies.…”
Section: Introductionmentioning
confidence: 99%